Present state of lake studies from satellite altimetry – a case study in Poland - Bernatowicz, Anna; Lyszkowicz, Adam (International Conference “Environmental Engineering”, 2017)
Satellite radar altimetry is a successful technique for monitoring elevations of continental surface water. The surface water level is measured within a terrestrial reference frame with a repeatability varying from 10 to 35 days depending on the orbit cycle of the satellite. With several decades of technique refinement; current data processing can be fairly simple or complex depending on the mission and the tracking methods. Data acquisition is not affected by weather conditions; but the technique can have a number of limitations. However; the technique is sufficiently advanced to have allowed a number of inland water case studies. Focusing on the large lakes; the links between lake evolution and the local climate cycle on seasonal to interannual timescales can be explored; and water storage balance for water management also can be brought into focus. This article reviews present day lake level monitoring and the case study of the Łebsko lake in Poland. First the basic principle of satellite altimetry, current altimetry missions, hydrology application and lake and reservoir altimetry measurements in web sites are shortly describe. Next the investigation of the surface of the Łebsko lake in Poland was carried out. From our study reveals that altimetry could provide a promising future for true global lake studies with height and width observation of all targets with centimeter accuracy.
Keywords: satellite altimetry; water surface altitude; hydrology altimetry product; inland water body